Influence of organization change to knowledge assets - Edrea, anak Mandak (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The purpose of this study is to determine the impact of organization change to the organization knowledge assets. The conceptual framework developed for this study examine the relationship of sharing culture, individualism, organization structure, employees’ turnover and training to organization knowledge, itself is divided into tacit and explicit knowledge. This study focused on descriptive and quantitative data obtained from survey forms distributed based on stratified sampling to the employees of Hitachi Global Storage Technologies, Samajaya Free Industrial Zone in Kuching. These data were analyzed using Pearson’s Correlation and Multiple Regression to understand the relationship between the variables. Based on the findings, training activities were found to have a strong influence in increasing the knowledge assets especially on tacit knowledge after the organization change. Organization structure post change may have been simplified by elimination of overlapping positions which allow or ease the flow of information from the source to the receiver. Increase in turnover seems to contribute to the explicit knowledge, which is against the indication that employees’ outflow causing a decrease in knowledge. A lean organization gives the opportunity for employees to be specialized and focused on their work area. In future research, it is suggested to include an in depth study on training which may include type of trainings and development programs which are considered value adding to the company. It should include larger scale surveys to allow more systematic analysis of the causalities resulted from organization change and also considering the inclusion of qualitative data to uncover unexplained factors.